2020
DOI: 10.1088/1361-6579/abb75e
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycling performance and sleepiness during an extended ride on a dynamic simulator: relationship with stress biomarkers

Abstract: Objective: Powered two-wheelers (PTW) make up a large proportion of fatal accidents. The aim of this study was to investigate the effects of time-of-day and total sleep deprivation (SD) on simulated motorcycling performance during extended riding sessions (60 min), while evaluating stress mechanisms. Approach: A total of 16 healthy males participated in four simulated motorcycling sessions at 07:00, 11:00, 15:00 and 19:00, including city (8 min), country (2 min) and highway pathways (40 min), after a normal ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…The CgA is released along with catecholamines from the adrenal medulla and sympathetic nerve endings and is additionally seen as a biomarker of stress [ 24 ], but we are not aware of any data on sleep restriction. At SR5, we found no change in sCgA levels, as previously observed at 7 h after total sleep deprivation, whereas in this latest study, we observed an acute increase after a 60 min motorcycle riding session [ 51 ]. In our study, SR-RT and SR-NS conditions influenced sAA and CgA levels, particularly in recovery from severe sleep restriction.…”
Section: Discussionsupporting
confidence: 71%
“…The CgA is released along with catecholamines from the adrenal medulla and sympathetic nerve endings and is additionally seen as a biomarker of stress [ 24 ], but we are not aware of any data on sleep restriction. At SR5, we found no change in sCgA levels, as previously observed at 7 h after total sleep deprivation, whereas in this latest study, we observed an acute increase after a 60 min motorcycle riding session [ 51 ]. In our study, SR-RT and SR-NS conditions influenced sAA and CgA levels, particularly in recovery from severe sleep restriction.…”
Section: Discussionsupporting
confidence: 71%
“…6A. There was no significant correlation between BAccs and SSS reports (r(20)=.32, p=.14, BF 10 =.47), suggesting that subjective sleepiness did not express all of the objective effects of sleep deprivation, at least as captured by our voice classifiers.…”
Section: Resultsmentioning
confidence: 76%
“…The psychomotor vigilance test (19), often used in research settings, tests for the ability to respond quickly to infrequent stimuli, with slower reaction times being used as a marker of attentional lapses. More recently, new approaches have attempted to leverage the concentration ok key molecules in the urine, saliva or breath to quantify sleepeiness (20). Although these objective methods are complementary to subjective reports, they are often costly, time consuming, or difficult to deploy outside of laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…This was chosen i) to approximately estimate time on task kinetic and ii) because a 3-minute task is often used to evaluate cognitive fatigue. 31 …”
Section: Methodsmentioning
confidence: 99%